Production of Biofuel (Bioethanol) from Vigna Radiata Biomass - Pranondo, Diky; Niko Pratama; Savira Dyah Istiqlawati; Tania Dwi Putri (International Journal of Contemporary Sciences (IJCS), 2024)
Indonesia is one of a few country that has the high rate consumption of fossil fuels. Bioethanol is considered as an important renewable fuel to partly replace fossil-derived fuels. This sustainable technology has increased tremendously with decreasing world crude oil reserves while the energy prices continually increasing. One of the potential raw materials for bioethanol production is mung bean (Vigna radiata). Mung bean is seasonal crops and grow almost in all region of Indonesia. Mung beans can be raw material for bioethanol production  because in 50 grams of mung beans contain 18.41% glucose. Bioethanol production begins with hydrolysis 50 grams of mung beans in 200 ml of water as much as 4 samples until it becomes pulp. The process was followed by the fermentation process by using yeast (Saccharomyces cerevisiae) for four days with variation of a weight of 1 gram, 2 grams, 3 grams and 4 grams. The last process is distillation, it used to separate water and ethanol. Sample 2 shows the optimum ratio for bioethanol production which is 50 grams of mung beans and 2 grams of yeast (50:2). The optimum result from experiment obtained 6.4615% ethanol and 1.3371 refractive index